Pharmacokinetics, pharmacodynamics and safety assessment of multiple doses of soticlestat in healthy volunteers. Issue 6 (31st January 2022) - Wang, Shining; Chen, Grace; Merlo Pich, Emilio; Affinito, John; Cwik, Michael; Faessel, Hélène M.
Abstract : Aims: Soticlestat, a first‐in‐class inhibitor of cholesterol 24‐hydroxylase (also known as cytochrome P450 46A1), is currently in development for the treatment of developmental and epileptic encephalopathies. Here, we report safety, tolerability, pharmacokinetic and pharmacodynamic outcomes from a phase I, randomized, double‐blind, placebo‐controlled, multiple‐rising‐dose study of soticlestat in healthy adults. Methods: Five cohorts of healthy subjects (n = 8 each, randomized 6:2 soticlestat:placebo) received oral soticlestat 100‐600 mg once daily (QD) or 300 mg twice daily (BID) for 10‐14 days. Serial blood and urine samples were obtained on days 1, 7 (blood only) and 14. Results: S oticlestat in the dose range 100‐400 mg/day for up to 14 days was generally well tolerated. In total, 45 treatment‐emergent adverse events (TEAEs) were reported; most (91%) were transient and mild in intensity. Two subjects experienced TEAEs leading to discontinuation: one receiving soticlestat 600 mg QD reported a severe event of acute psychosis; another receiving 300 mg BID reported a mild event of confusional state. Steady‐state exposure to soticlestat increased in a slightly greater than dose‐proportional manner across the dose range 100‐400 mg QD. Peak plasma concentrations were reached within 0.33‐0.5 hour, and soticlestat elimination half‐life was approximately 4 hours. Renal excretion of soticlestat was negligible. Soticlestat 100‐400 mg QD reduced 24 S ‐hydroxycholesterol levels by 46.8 (coefficient of variation [CV%] −9.2) to −62.7% (CV% −7.3) at steady state; values of enzymatic inhibition were compatible with antiepileptic effects observed in preclinical models. Conclusion: The pharmacokinetic and pharmacodynamic profiles of soticlestat characterized here provided a data‐driven rationale for clinical trial dose selection.